Implikasi Konsep Islamisasi Ilmu Pengetahuan Ismail Raji Al-Faruqi - Poppy Rachman (Institut Ilmu Keislaman Zainul Hasan Genggong, 2020)
This research is entitled Implications of the Concept of Islamization of Ismail Raji Al-Faruqi Science. Science is important in human life. God put knowledge as a matter that must not be abandoned. During this time the Islamic religion is believed to have a very important role in coloring the building of science. But in reality, the Muslim community seems to be forced to carry out secular teachings in life due to the swift currents of secularization. This condition is a concern of Islamic thinkers, because it can endanger the Islamic faith. It is in connection with this concern that ideas or ideas about the Islamization of science emerge as an attempt to neutralize the influence of modern western science. Al-Faruqi was one of the thinkers about Islamization. How is the concept of Islam? and what are the implications for life in Indonesia? The Islamization of knowledge is not only a discourse, but requires real implications to be useful for the wider community. Al-Faruqi has sought to realize the Islamization of knowledge by establishing Islamic study groups. The movement is carried out by sticking to the principles of monotheism so as not to deviate from religious teachings. Some developments have also taken place in Indonesia in response to the Islamization of science, including: the establishment of Islamic-based schools and the rise of cooperatives and Islamic banks.